Impact of Merchandising and Social Media on the Brand Positioning of Football Teams - Villalta Hurel, Edgar Josue; Ramón Herrera, Stalin Rafael; Sarmiento Chugcho, Carlos Bolívar; Guerrero Carrasco, Martha Jaroslava (Revista Universidad de Guayaquil, 2025)
In Ecuador, for a brand to position itself and maintain a presence in the market, it must make use of social media and implement merchandising strategies to enable a football team to penetrate the market. Effective communication on these platforms increases consumer awareness and trust. In other words, social platforms not only enhance fan engagement but also help merge promotional efforts with brand value. Likewise, a strong digital image is essential for brand loyalty and appreciation, and it is crucial that this image be vibrant and captivating. Given the quantitative design, the study selected 384 football fans through a non-probabilistic sampling method. Very high reliability and validity were observed in the constructs used, which showed acceptable values: Cronbach’s alpha of 0.89 for MER and 0.90 for PM, and AVE values above 0.65. Correlation coefficients also fully confirmed discriminant validity. In another analysis, the structural model indicated that merchandising strategies had a direct and significant effect on brand positioning (0.61, p < 0.001), and social media acted as a mediator in this relationship, with an indirect effect of 0.17, p < 0.001. The net result was that the study concluded that merchandising marketing strategies, complemented by brand campaigns, made it possible to achieve the desired positioning, which was the main objective of the analysis.